2015
DOI: 10.1186/s12887-015-0335-6
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of obesity classification between body mass index and percent body fat among school children in Saudi Arabia

Abstract: BackgroundIn Saudi Arabia, where childhood obesity is a major public health issue, it is important to identify the best tool for obesity classification. Hence, we compared two field methods for their usefulness in epidemiological studies.MethodsThe sample consisted of 874 primary school (grade I-IV) children, aged 6–10 years, and was obtained through a multi-stage random sampling procedure. Weight and height were measured, and BMI (kg/m2) was calculated. Percent body fat was determined with a Futrex analyzer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…Excess body weight was identified in 20.0% of the participants in this study, and obesity in 5.0%. Similar proportions were reported by researchers in Greece, who found excess weight and obesity in 22.4% and 6.5% of their participants, respectively ( 15 ). They also noted that excess body weight was more common in boys than in girls.…”
Section: Discussionsupporting
confidence: 87%
“…Excess body weight was identified in 20.0% of the participants in this study, and obesity in 5.0%. Similar proportions were reported by researchers in Greece, who found excess weight and obesity in 22.4% and 6.5% of their participants, respectively ( 15 ). They also noted that excess body weight was more common in boys than in girls.…”
Section: Discussionsupporting
confidence: 87%
“…A variety of cutoff points and references were used in the studies to define overweight and obesity in Saudi Arabian children. Several studies (n = 6) used the WHO (1995) criteria (Al-Almaie, 2005;Al-Mohaimeed et al, 2015;Al-Rowaily et al, 2007;Al-Rukban, 2003; Farghaly et al, Prevalence of overweight and obesity were 20% and 11%, respectively. Overweight was higher among students with father in private work (p < .01) and among students with highly educated mothers (p = .008).…”
Section: Determining Childhood Overweight and Obesitymentioning
confidence: 99%
“…A study with adults has revealed discrepancy between overweight by BMI and overweight and excess fat by Fat% in adults 11 . Similarly, moderate concordance between BMI indicators and fat percentage in the estimation of body adiposity was observed in children and adolescents 12,13 . Therefore, the aim of this study was to verify the prevalence and concordance of overweight by BMI and excess body fat by Fat% in adolescents of both sexes from the cities of Rio Branco (AC) and Porto Velho (RO).…”
Section: Introductionmentioning
confidence: 95%